2009
DOI: 10.1073/pnas.0904695106
|View full text |Cite
|
Sign up to set email alerts
|

Plant sex and the evolution of plant defenses against herbivores

Abstract: Despite the importance of plant-herbivore interactions to the ecology and evolution of terrestrial ecosystems, the evolutionary factors contributing to variation in plant defenses against herbivores remain unresolved. We used a comparative phylogenetic approach to examine a previously untested hypothesis (Recombination-Mating System Hypothesis) that posits that reduced sexual reproduction limits adaptive evolution of plant defenses against arthropod herbivores. To test this hypothesis we focused on the evening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
148
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(154 citation statements)
references
References 63 publications
3
148
3
Order By: Relevance
“…Prior theoretical work has predicted the evolution of greater plant defense in sexual vs. asexual taxa, potentially as a result of differential recombination rates (24) or reduced mutation accumulation (25). This prediction has been supported by a large study of constitutive plant resistance in the Onagraceae (evening primroses) (26) and complements research on the role of parasites in the evolution of sex (27). However, it remains unknown whether variation in sexual reproduction should similarly influence defense evolution, in part because recombination rates may be widely variable in all but extremely or obligately selfing taxa.…”
mentioning
confidence: 54%
See 3 more Smart Citations
“…Prior theoretical work has predicted the evolution of greater plant defense in sexual vs. asexual taxa, potentially as a result of differential recombination rates (24) or reduced mutation accumulation (25). This prediction has been supported by a large study of constitutive plant resistance in the Onagraceae (evening primroses) (26) and complements research on the role of parasites in the evolution of sex (27). However, it remains unknown whether variation in sexual reproduction should similarly influence defense evolution, in part because recombination rates may be widely variable in all but extremely or obligately selfing taxa.…”
mentioning
confidence: 54%
“…Future work could compare these results with responses to herbivores with different feeding modes or host ranges. Although sex per se (vs. asexuality) is long thought to have been favored in part by coevolution of antagonistic interactions (26,27,52), we have demonstrated that such interactions may also coevolve with variation in the mode and expression of sexual reproduction. These findings also complement prior research showing that intraspecific variation in mating systems (32) and associated traits such as sex (33) can alter plant defense trait expression, with the potential for herbivores to influence the evolution and maintenance of plant reproduction within populations (30,32).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…32 It limits the entry of pathogens by blocking physically or increasing the leaf toughness that reduces the feeding by herbivores, and also decreases the nutritional content of the leaf. 33 Lignin synthesis has been found to be induced by herbivory or pathogen attack and its rapid deposition reduce further growth of the pathogen or herbivore fecundity. 33 Increase in expression of lignin associated genes (CAD/ CAD-like genes) in plants infected with pests and pathogens have been documented.…”
Section: Mechanisms Of Plant Defense Against Insect Herbivoresmentioning
confidence: 99%